ANALYSIS OF THE IMAGERY RELATING TO THE CARPE DIEM IDEA IN THE POEM “THE RUBAIYAT” - Safnidar Siahaan (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2018)
This research is presented to discuss about the imagery of the poetry entitled “The Rubaiyat”. The Rubaiyat is a poem in the 11th century written by a Persian poet named Omar Khayyam. One of the poets who had translated the poem "The Rubaiyat" into English was Edward FitzGerald in 1859, which attracted much controversy. The Rubaiyat is a poem containing with the religious teachings and philosophical symbols that produce a harmonious effect. In this research, the writer used qualitative method with descriptive approach. The writer used the theory of Imagery in analyzing the use of imagery in the poetry relating the idea of carpe diem. Furthermore; the writer collects the data from the poem “The Rubaiyat” written by Omar and classify the kinds of imagery refers to carpe diem ideas that can be found in the poem